ANALISIS USAHA MIKRO, KECIL DAN MENENGAH PENGOLAHAN KERUPUK IKAN GABUS DI KABUPATEN BANJAR - Yarna Hasiani (Universitas Lambung Mangkurat, 2017)
This study aims to (1) analyze the performance of technology processing business cracker cork fish in Banjar district; and (2) analyze the factors that affect revenue processing business cracker cork fish in Banjar district. The research was conducted in the village of Sungai Alang, Karang Intan Subdistrict, Banjar District, as one of the villages located Groups Processors and Marketers (poklahsar) fish crackers cork in Banjar Regency, with the object of research the processing of fish cracker cork incorporated in poklahsar fish cracker cork. The results showed that the performance of technology, processing business cork fish crackers develops well, after the processors belonging to the group processors and marketers (poklahsar), which is characterized by increasing the quantity and quality of production. Operating revenues fish cracker processing real cork influenced by the volume of fish that is processed, the amount of the loan capital and business scale, where the regression coefficient of each variable with the probability of positive-value <0.01 or valid at test level of 99%.